ANALISIS KINERJA PEGAWAI DALAM MEWUJUDKAN PROGRAM INOVASI PELAYANAN PUBLIK PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA KENDARI - Aminuddin; La Manguntara; Sana Ria; Nur Azizah (Journal Publicuho, 2024)
The purpose of this study was to determine the performance of employees in realizing public service innovation at the Population and Civil Registration Office of Kendari City based on indicators of work quality, timeliness, ability, initiative and communication, the type of research used was qualitative research. The results showed that the performance of employees of the Population and Civil Registration Office of Kendari City in realizing the public service innovation program requires communication skills and a proactive attitude from employees. Although employees have been meticulous as well as highly committed to working, efforts are still needed to improve the quality of work through training and technical guidance (bimtek). In addition, the timely performance of employees in working is one of the advantages that support the success of this innovation program. Timeliness in completing tasks and providing services to the community not only reflects employee professionalism but also increases public trust in the Population and Civil Registration Office of Kendari City. Thus, despite challenges in terms of communication skills and initiative, employees' on-time performance can be a foundation for improving other aspects of public service.